Dependence on resources and cooperation networks of the National Olympic Academies - Salepi, P.; Georgiadis, K.; Kriemadis, A.; Travlos, A. (Journal of Human Sport & Exercise, 2022)
This study seeks to identify the strategic and operational factors necessary for the effective operation of the International Olympic Academy (IOA), and of the National Olympic Academies (NOAs). It applies Resource Dependence Theory (RDP) and Inter-organizational Relationships Theory (IOR) to the institutional environment of the NOAs. A set of exploratory semi-structured interviews were conducted with key stakeholders from the International Olympic Committee (IOC), IOA, NOAs and Academics. A thematic analysis of the interview data provided themes to be incorporated into a questionnaire conducted with NOA directors and NOC officials focusing on relationships of the NOAs with other organisations and the implications for their autonomy. The nature of the field of NOA activity and its environment, is such that, for many NOAs, it is beset by an imbalance of power. This is reflected in the resource dependency of many NOAs on, in particular, NOCs and ultimately the IOC for legitimacy, human, financial and physical resources. The paper highlights a number of ways in which these relationships might be modified for the benefit of all the organisations involved.